Turning a corner. (Economist, 2000)
Europe's biggest software firm, SAP, missed out on the Internet and had a couple of bad years, but the good times may be just around the corner for the company. The company has an impressive new Internet platform, has made strategic partnerships with two former rivals, and has just secured the biggest deal in its history: to extend its web-based applications to 230,000 employees at Nestlé. Part of the problem for SAP was that co-chairman Hasso Plattner has always had an ambivalent view of America, distrusting the “froth” in its technology sector. North America was by far SAP's largest market, but SAP America was never included in the highest councils at the firm's headquarters in Walldorf, Germany. Now, however, the once-haughty SAP claims to have learned its lessons and changed the way it operates. SAP is now working to turn its core system designed for client/server computing into a fully fledged e-business platform. At the center of this effort is the mySAP.com platform. Details of this application, how it works, and how it has changed how SAP operates are provided.